Optymalna niejednorodność plastyczna skręcanego pręta ze względu na nośność graniczną - J. Majerczyk-Gómulkowa; A. Mioduchowski (Engineering Transactions, 1969)
Here considered are torsioned prismatic bars with a transverse, continuous plastic nonhomo-geneity. On the basis of the Neustadt-Halkin method, the necessary conditions for such a distribution of this nonhomogeneity, which offers a maximum limiting load capacity were obtained. A straightforward graphical interpretation of these conditions is given, discussed in detail upon the example of a prismatic bar with a square cross-section. The solutions are also presented for bars with septagonal, circular and elliptical cross-sections.